2009
DOI: 10.1111/j.1365-2265.2008.03451.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peripheral administration of synthetic human glucose‐dependent insulinotropic peptide (GIP) on energy expenditure and subjective appetite sensations in healthy normal weight subjects and obese patients with type 2 diabetes

Abstract: We report here for the first time that GIP infusion may impact on resting EE and subjective appetite sensations in normal weight healthy subjects and further studies with larger numbers of subjects are required to help define more conclusively the precise role of GIP in energy balance in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 32 publications
2
50
2
Order By: Relevance
“…The administration of GLP1 receptor agonists in T2DM improves glucose homeostasis, while it is followed by a dose-dependent weight loss compared with placebo (10)(11)(12). Furthermore, GIP, another incretin, has been associated with a decrease in resting energy expenditure in healthy humans (13). Ghrelin, discovered as a natural ligand of the GH secretagogue receptor type 1a, is a gut-brain peptide with somatotropic, food intake-increasing and adipogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The administration of GLP1 receptor agonists in T2DM improves glucose homeostasis, while it is followed by a dose-dependent weight loss compared with placebo (10)(11)(12). Furthermore, GIP, another incretin, has been associated with a decrease in resting energy expenditure in healthy humans (13). Ghrelin, discovered as a natural ligand of the GH secretagogue receptor type 1a, is a gut-brain peptide with somatotropic, food intake-increasing and adipogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have founded that postprandial GIP response was inversely related to the subsequent feeling of satiety (5,12,13). On the other hand, positive (14) or neutral (9,10,15) correlation between postprandial GIP and satiety were also observed.…”
Section: Introductionmentioning
confidence: 70%
“…Daousi et al [26] reported that intravenous infusion of GIP reduces REE in healthy humans, suggesting that GIP has acute effects on energy catabolism. In the present study, blood GIP levels were reduced after consumption of steamed WB and, simultaneously with the decrease in the blood GIP levels, fat utilization was increased in mice fed the WB diet.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic deficit in GIP-secreting K cells enhances energy expenditure and prevents high-fat diet-induced obesity in mice [25]. In contrast, intravenous administration of GIP to healthy lean men lowers resting energy expenditure (REE) [26]. In our previous study, we found that the dietary components that control GIP secretion, such as diacylglycerol [27], 1-monoolein [28], and RS4-type-resistant starch [29], increase postprandial fat utilization and prevent high-fat diet-induced obesity in mice.…”
Section: Introductionmentioning
confidence: 99%